Être expulsé ou interné à Djelfa aux siècles derniers (1893 ; 1942) - Danièle Iancu-Agou (Revue des Mondes Musulmans et de la Méditerranée)
This article is a story of frienships. Professor Simon Schwarzfuchs introduced me, a long time ago, to a testimony, translated by himself from yiddish, of Benjamin Lubelski, ancient prisoner in the camp of Djelfa (1942); another friend, Hugues-Jean of Dianoux, archivist-paleographer and retired diplomat, told me about the sad episode that occurred at the end of the XIXth century (1893), the imprisonment of a Khmer in Djelfa, the son of a Cambodian monarch ! The meeting ten years ago, in Jerusalem, of Benjamin Lubelski (died since), created the moral necessity to publish his testimony, and to enrich it with elements on these other exiles: the prince Duong Chakr died in Djelfa, and famous prisoner Max Aub, who fought for the Spanish Republic and whose writings on " The graveyard of Djelfa " oddly respond to the narration of Lubelski. Finally, a last link in this chain of friendship, Marceau Gast, familiar with the "boundaries of Sahara", contributed to the publication of this text.